Occult Charm and Social Ills: Vernon Lee’s “A Wicked Voice” and George Du Maurier’s Castrated Texts - Kehler, Grace (Romanticism on the Net, 2004)
AbstractThis article explores the late Victorian fascination with the defunct voice of the operatic castrato as manifest in two texts by Vernon Lee — Studies of the Eighteenth Century in Italy and “A Wicked Voice” — and in George Du Maurier’s Trilby. Each text imagines a revenant castrato, using the life and body of the violated singer as a source of enchantment and endless aesthetic speculation. Though these texts implicitly acknowledge their exploitive nature, they lack the self-mastery to resist the pleasure of making the surgically altered and socially wanting castrato serve perfection fantasies. Still, the representations of the revenant castrato bear with them a social and moral history that interrupts the pleasure of speculation and highlights the brutality of what art lovers have nominated as an ideal.